How Much Does Irrelevant Speech Impair Employees' Work Performance in Open-Plan Offices?. (October 2013) - Jahncke, Helena
When people are talking in the background of an open-plan office it can be experienced as disturbing. However, it is not well specified how much irrelevant speech actually disrupts performance. The aims of the present study were, first, to investigate how much cognitive performance is impaired by irrelevant background speech with varying degrees of speech intelligibility, and second, to determine whether some office-related tasks are more susceptible than others. The results showed that cognitive performance decreased as a function of background speech intelligibility, the higher the intelligibility depicted by the Speech Transmission Index (STI), the worse the performance. The results indicated that the STI-value should be less than 0.50 (between the speaker and the listener), to avoid a negative influence on performance. Further, performance was more impaired by background speech if the focal task required episodic memory and rehearsal — such as word memory and information search. Interestingly, some tasks were insensitive for speech. This study also shows that the efforts to minimize speech intelligibility will yield increases in cognitive performance with a varying degree, depending on the type of focal task.